2006
DOI: 10.1161/01.hyp.0000222003.28517.99
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Injury Underlies the Glomerulopathy of Dahl Salt-Hypertensive Rats and Is Reversed by Aldosterone Blocker

Abstract: Abstract-Recent clinical studies implicate proteinuria as a key prognostic factor for renal and cardiovascular complications in hypertensives. The pathogenesis of proteinuria in hypertension is, however, poorly elucidated. Podocytes constitute the final filtration barrier in the glomerulus, and their dysfunction may play a pivotal role in proteinuria. In the present study, we examined the involvement of podocyte injury in Dahl salt-hypertensive rats, an animal model prone to hypertensive glomerulosclerosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
209
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(232 citation statements)
references
References 57 publications
(64 reference statements)
19
209
1
3
Order By: Relevance
“…We confirmed that the serum concentration of aldosterone did not increase in the DS+HS group compared with that of the DS+NS group. Recent basic studies have demonstrated that MR activation is important in the etiology of cardiovascular and renal diseases not only in highaldosterone status but also in low-aldosterone hypertension, 12,36 which are consistent with our results. How is MR activated in lowaldosterone hypertension?…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed that the serum concentration of aldosterone did not increase in the DS+HS group compared with that of the DS+NS group. Recent basic studies have demonstrated that MR activation is important in the etiology of cardiovascular and renal diseases not only in highaldosterone status but also in low-aldosterone hypertension, 12,36 which are consistent with our results. How is MR activated in lowaldosterone hypertension?…”
Section: Discussionsupporting
confidence: 93%
“…Nagase et al [34] reported that eplerenone improved podocyte damage and retarded the progression of proteinuria and glomerulosclerosis. Iwakura et al showed that in 111 patients with bilateral hyperaldosteronism treated with mineralocorticoid receptor antagonists, urinary albumin excretion and eGFR were significantly decreased at 12 months after treatment; these results were consistent with the results from our study [35].…”
Section: Discussionmentioning
confidence: 99%
“…9,31 Further evidence suggests a role of oxidative stress in the pathogenesis of podocyte injury in Aldo-infused rats. 3 However, the source of Aldo-induced oxidative stress in podocytes is still poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Aldo causes podocyte injury in vivo and in vitro, and Aldo blockade is therapeutic in renal injury. 5,[7][8][9] However, the underlying mechanism for Aldoinduced injury in the kidney (in general) and in the podocytes (in particular) is not well understood.Podocytes are terminally differentiated, high-energy required cells that have lost mitotic activity, and typically do not proliferate after injury. 10 Mitochondria (mt) dysfunction (MtD) is involved in several diseases and progressive disease processes, including glomerulosclerosis, in which podocyte injury is a crucial event in sclerosis formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation